China’s Quest for Oil in Africa: An Ethical Perspective - Sinharay, Soumyadeep (Prabandhan: Indian Journal of Management, 2010)
Business Ethics (A.C. Fernando, 2001) are applied ethics that studies moral standards and shows how these apply to the systems and organizations involved in business. Business ethics deals with ethics in businesses, dilemmas and conflicts in decision making, accountability and transparency to shareholders/ stakeholders and is consistent with sustainable development. Business in the long term should be sustainable with environmental, social and economic concerns. It has a proven effect on the long term sustainability of modern day businesses. Thus the study of Business ethics is of prime importance in the present business environment. Any ethical issue involves the different stakeholders like the owners, customers, investors, society etc. An ethical dilemma occurs when the interests of any one of these stakeholders is compromised. So, any ethical issue should be analyzed in the light of the above mentioned stakeholders.